Odpowiedź :
zad 2
a)
5x+2=7-3x
5x+3x=7-2
8x=5 / : 8
x=5/8
b)
- 6 ( x + 1 ) = 24
-6x-6=24
-6x=24+6
-6x=30 / :(-6)
x= -5
c)
- 7 ( x–2 ) = 3x – 1
-7x +14 =3x-1
-7x - 3x= -1-14
- 10x= -15 / :(-10)
x= 3/2
d)
- 0,5 ( - x – 6 ) = - x
0,5x +3= -x
0,5x +x = -3
1,5x = -3 / : 1,5
x= -2
e)
x/5 - 3 = x + 1/5
x- 15= 5x+1
x-5x =1 +15
-4x =16 /:(-4)
x= -4
Szczegółowe wyjaśnienie:
Zad 2
a) 5x + 2 = 7 - 3x
5x + 3x = 7 - 2
8x = 5
x = 5/8
b) -6 (x + 1) =24
x + 1 = -4
x = -4 - 1
x = -5
c) -7(x-2) = 3x - 1
-7 x + 14 = 3x - 1
-7x - 3x = -1 - 14
-10 x = -15
x = 3/2